2021
DOI: 10.3390/jof7121050
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Strain Trichoderma asperellum 6S-2: An Efficient Biocontrol Agent against Apple Replant Disease in China and a Potential Plant-Growth-Promoting Fungus

Abstract: A study was conducted for endophytic antagonistic fungi obtained from the roots of healthy apple trees growing in nine replanted orchards in Shandong Province, China. The fungi were assessed for their ability to inhibit Fusarium proliferatum f. sp. malus domestica MR5, a fungal strain associated with apple replant disease (ARD). An effective endophyte, designated as strain 6S-2, was isolated and identified as Trichoderma asperellum. Strain 6S-2 demonstrated protease, amylase, cellulase, and laccase activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 82 publications
(102 reference statements)
2
18
0
1
Order By: Relevance
“…proliferatum, and F. moniliforme were convincingly the major pathogenic fungi causing ARD in China after investigations of the main apple-producing regions. Fusarium produces a variety of toxins that cause root necrosis and decay, resulting in short, withered, and dead plants, and the destruction of the microbial community structure. , In the present study, the copy number of these four pathogenic Fusarium fungi exhibited a downward trend over time under the different treatments (except MBF) (Figure ), which may be related to the changes in the soil temperature and moisture (Figure S5). Moreover, the copy numbers of the four pathogenic Fusarium fungi in T1 and T2 were significantly lower than those in CK, providing a strong evidence that adding N/P from an external source reduced the number of harmful microorganisms, which is consistent with the studies of Utkhede and Simth and Wang et al At a given time point, the number of Fusarium was related to the type of fertilizer.…”
Section: Resultssupporting
confidence: 50%
“…proliferatum, and F. moniliforme were convincingly the major pathogenic fungi causing ARD in China after investigations of the main apple-producing regions. Fusarium produces a variety of toxins that cause root necrosis and decay, resulting in short, withered, and dead plants, and the destruction of the microbial community structure. , In the present study, the copy number of these four pathogenic Fusarium fungi exhibited a downward trend over time under the different treatments (except MBF) (Figure ), which may be related to the changes in the soil temperature and moisture (Figure S5). Moreover, the copy numbers of the four pathogenic Fusarium fungi in T1 and T2 were significantly lower than those in CK, providing a strong evidence that adding N/P from an external source reduced the number of harmful microorganisms, which is consistent with the studies of Utkhede and Simth and Wang et al At a given time point, the number of Fusarium was related to the type of fertilizer.…”
Section: Resultssupporting
confidence: 50%
“…The isolation procedure was based on that described in Wang et al with slight modification of the separation scheme [ 39 ]. First, the roots were washed with deionized water, soaked in 75% alcohol for 10 min, soaked in 4% sodium hypochlorite for 10 min, soaked in sterile water for 10 min, and rinsed in sterile water 4–5 times.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier research, we isolated an apple root endophyte designated strain 6S-2 and identified it as T. asperellum. 6S-2 was shown to be an efficient biocontrol agent against ARD in China and had potential plant-growth-promoting activity [25]. The aims of the present study were therefore (i) to characterize the effects of 6S-2 fertilizer application on the growth of apple plants in greenhouse, pot, and field experiments; (ii) to analyze changes in the soil microbial community structure after 6S-2 fertilizer application (especially the abundances of Trichoderma and harmful Fusarium species); (iii) to document changes in root exudates of M. hupehensis Rehd seedlings after 6S-2 fertilizer application and the relationship between these exudates and the soil microbial community structure; and (iv) to gain insight into the mechanisms by which 6S-2 fertilizer alleviates ARD.…”
Section: Introductionmentioning
confidence: 99%